Bio-surfactant: a green and environmentally benign reaction medium for ligand-free Pd-catalyzed Mizoroki-Heck cross-coupling reaction in water - Patil, Seema P.; Jadhav, Sanjay N.; Rode, Chandrashekhar V.; Shejwal, Rajendra V.; Kumbhar, Arjun S. (Transition Metal Chemistry, 2020)
A simple and efficient protocol for the ligand-free Mizoroki-Heck coupling reaction of various aryl bromides with different olefins has been reported by using in situ generated PdNPs of size 5-10 nm in aqueous solution of bio-surfactant. The bio-surfactant used in this study is a saponin extract of the seeds of pericarps (pods) of theAcacia concinnaplant. The in situ generated PdNPs have been characterized by various techniques such as HRTEM, EDS and XPS. The influence of various parameters such as the nature and amount of bases, the nature of Pd precatalysts as well as the effect of temperature has been investigated on Mizoroki-Heck coupling reaction. The generated PdNPs significantly coupled the various aryl bromides with different olefins in aqueous extract of the seeds of pericarps (pods) of theAcacia concinnaplant at 100 degrees C. [GRAPHICS] .